Early Holocene Occupation of the Forest-Steppe Ecotone of Southern South America: Evidence from Casa de Piedra de Roselló Cave (Chubut, Patagonia Argentina) - Castro, Analia (2017)
This paper presents information on the site called Casa de Piedra de Roselló, located near the town of Aldea Beleiro in southwestern Chubut Province, Argentina. It includes the latest dates obtained there, which fix human occupation of the area at ca. 9000 cal yr BP. This early chronology–currently regionally comparable only to that obtained from Baño Nuevo 1 in the Republic of Chile–make Casa de Piedra de Roselló outstanding, since archaeological studies of it will contribute in a general way to deepening our understanding of the ways of life of human societies that inhabited Patagonia during the early Holocene.